La traductologie canadienne : ancrage européen, tropisme anglo-américain - Annie Brisset (Romanica Wratislaviensia)
History and politics account for the development of Translation Studies in Canada. In 1969 when the Official Languages Act compels the Canadian government to communicate both in French and English to restore the rights of the francophone minority, translators are in short supply. Translation thus becomes an academic discipline. An inventory of Canadian books on translation published during the ensuing fifty years (1970–2020) brings to light two main stages in the evolution of translation research. During the first two decades (1970s–1980s), didactics and terminology development figure prominently. At the crossroads of European and American poststructuralist works, Canadian translation criticism emerged at the turn of the1990s. By setting itself in the descriptive, target-oriented paradigm (Tel Aviv-Louvain school of thought), it broke away from the hermeneutic-poetic paradigm epitomized by Meschonnic. Feeding upon French Theory (Bourdieu, Derrida, Foucault) and Cultural Studies (Bhabha, Spivak), the main underpinnings of American postcolonialist scholarship, it aggregated around cross-cultural objects of study, with the concept of translation now extending to the interaction of cultures. Sociological approaches to translation represent the second most important research area. Today, these approaches are superseded by new complex, interdisciplinary models. Attention is shifting towards espistemology while digital supports and new practices bring about new theoretical queries, new technological tools, and didactic models. Finally, with facts and figures in hand, we question the status of Translation Studies in French in a globalized editorial environment, where English reigns supreme.